2014
DOI: 10.1038/hr.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Combination of plasma-soluble fms-like tyrosine kinase 1 and uterine artery Doppler for the prediction of preeclampsia in cases of elderly gravida

Abstract: The aim of this study was to determine the predictive value of the combination of plasma-soluble fms-like tyrosine kinase 1 (sFlt-1) and uterine artery Doppler for the detection of preeclampsia in women of advanced age at 16-18 weeks of gestation and to identify associations between other pregnancy complications and abnormalities of these combined tests. The maternal plasma sFlt-1 level was measured, and uterine artery Doppler was performed at 16-18 weeks of gestation in 314 cases of elderly gravida. The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Bolin et al [12] demonstrated that separate measurements of serum HRG and PI may predict pre-eclampsia, but by combining serum HRG and PI the accuracy increased. This is in line with this study in which a total accuracy of both reached 84.3% and in line with studies proposing a combination of biochemical and biophysical markers for a successful prediction of pre-eclampsia in early pregnancy [13,14,22,23].…”
Section: Figuresupporting
confidence: 92%
“…Bolin et al [12] demonstrated that separate measurements of serum HRG and PI may predict pre-eclampsia, but by combining serum HRG and PI the accuracy increased. This is in line with this study in which a total accuracy of both reached 84.3% and in line with studies proposing a combination of biochemical and biophysical markers for a successful prediction of pre-eclampsia in early pregnancy [13,14,22,23].…”
Section: Figuresupporting
confidence: 92%
“…Several key events have been shown to be involved in the early development of PE, including insufficient spiral artery remodeling and higher plasma levels of soluble fms-like tyrosine kinase-1. Higher plasma levels of soluble fms-like tyrosine kinase-1 has been shown to antagonize vascular endothelial growth factor, which causes abnormal spiral artery remodeling [31][32][33] ; therefore, vascular endothelial growth factor inhibitors have been used as a model of PE. 34,35 In addition, based on two predominant theories of PE (the locally chronic uterine placenta ischemia and hypoxia theory and the excessive activation of the maternal immune system theory), additional animal models of PE have been developed.…”
Section: The Effect Of Mgso 4 On the Pe And Seizure Modelsmentioning
confidence: 99%
“…Increasing evidence suggests that an exaggerated maternal systemic inflammatory response to pregnancy with an increase in the ratios of peripheral blood Th1/Th2 and Th17/ regulatory T cells, a systemic oxidative stress, as well as an imbalance between circulating angiogenic and anti-angiogenic factors plays a crucial role in the pathogenesis of the disease. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Endocannabinoids are endogenous ligands that bind to the similar receptor as delta-9-tetrahydrocannabinol (Δ 9 -THC), the most potent psychotropic constituent of marijuana. The most studied endocannabinoid is N-arachidonoylethanolamine (also known as anandamide), which is reported to have a central role in female reproduction, particularly in decidualization, 17 oviductal transport, 18 preimplantation embryo development, 19 timely embryo implantation and ensuring receptive uterine environment.…”
Section: Introductionmentioning
confidence: 99%